Biochemical parameters of blood internally during trichurosis invasion - E. V. Mykhailiutenko; O. V. Kruchynenko (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Many papers have been published on the spread of invasive diseases, but few cover the impact of parasites on the organism of the definitive host. It is known that blood tests provide a lot of information about the general health of animals. Reference values for blood tests have been established to interpret deviations from physiological parameters. A biochemical study will allow to assess the level of functioning of internal organs (liver, kidneys, pancreas, etc.) under helminth parasitism; to obtain information on metabolism (metabolism of lipids, proteins, carbohydrates); to determine the body's need for trace elements. Therefore, the study aimed to determine changes in blood serum biochemical parameters in nutria with trichuria. The study was conducted in the Dokuchaevsky Hunter, Poltava region, in autumn 2023. The article presents the results of biochemical parameters of blood serum of male nutria infected with Trichuris myocastoris in the chronic course of the disease. The mechanical, trophic, toxic, inoculatory, and allergic effects of nematodes on the organism of Myocastor coypus are reflected in the obtained indicators. Thus, the serum of the semi-aquatic rodent increased total protein content by 7.49 %. In the case of parasitism in nutria of Trichuris myocastoris, the total bilirubin increased to 6.38 μmol/l due to direct bilirubin (2.63 μmol/l). In the presence of a pathological process in the body of nutria caused by the circulation of the pathogen, the qualitative and quantitative composition of enzymes in the blood changed. The results indicate that in the case of spontaneous trichuria infection of nutria, the activity of aspartate aminotransferase and alkaline phosphatase in the blood serum of infected rodents differ significantly from those of healthy animals. At the same time, the serum of the semi-aquatic rodent has a significantly increased content of creatinine by 31.03 %, urea by 42.12 %, and uric acid by 35.9 %. Since some researchers believe that cholesterol may play a role in the pathogenesis, we analyzed this indicator. It should be noted that cholesterol levels increased by 13.54 %. The concentration of triglycerides tended to increase, but there was no reliable confirmation. A deepening of pathological changes accompanies the localization of the pathogen in the body, so a decrease in the amount of inorganic phosphorus to 2.02 mmol/l was noted. The results of the analysis indicate a long-term inflammatory process in the body of nutria.